2019
DOI: 10.15420/ecr.2019.28.2
|View full text |Cite
|
Sign up to set email alerts
|

Troponins, Acute Coronary Syndrome and Renal Disease: From Acute Kidney Injury Through End-stage Kidney Disease

Abstract: The diagnosis of acute coronary syndromes (ACS) is heavily dependent on cardiac biomarker assays, particularly cardiac troponins. ACS, particularly non-ST segment elevation MI, are more common in patients with acute kidney injury, chronic kidney disease (CKD) and end-stage kidney disease (ESKD), are associated with worse outcomes than in patients without kidney disease and are often difficult to diagnose and treat. Hence, early accurate diagnosis of ACS in kidney disease patients is important using easily avai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…15 Another cause of elevated troponin-T includes kidney failure with increased creatinine, but our patient was found to have a normal creatinine, making this less likely. 16 Finally, troponin can be elevated following preload-induced mechanical stretch or physiologic stretches in otherwise normal hearts. 14 Given the fluid overload in our patient, myocardial strain caused by preload-induced wall stress was determined to be the etiology of the elevated troponin, especially in the setting of hypertensive emergency, which can exacerbate myocardial strain.…”
Section: Discussionmentioning
confidence: 99%
“…15 Another cause of elevated troponin-T includes kidney failure with increased creatinine, but our patient was found to have a normal creatinine, making this less likely. 16 Finally, troponin can be elevated following preload-induced mechanical stretch or physiologic stretches in otherwise normal hearts. 14 Given the fluid overload in our patient, myocardial strain caused by preload-induced wall stress was determined to be the etiology of the elevated troponin, especially in the setting of hypertensive emergency, which can exacerbate myocardial strain.…”
Section: Discussionmentioning
confidence: 99%
“…In that regard, Dietl et al showed the convergence of hs-TnT in men and women post menopause with increasing age [19] . Subramanya et al demonstrated an increase in the left ventricular mass (LVM) as a result of an increasing androgen effect in postmenopausal women [20] . These findings provide a biologically plausible explanation for the increase in cardiac markers in men with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Our hypothesis is that SZC therapy will reduce the incidence of treatment-limiting hyperkalaemia in CKD-HF patients, allowing higher doses of RAASi therapy and therefore better clinical outcomes. Achievement of the participant’s target RAASi dose is the primary endpoint, and secondary endpoints include measures to assess safety in terms of hyperkalaemia, cardiovascular risk in terms of troponin T levels [ 19 , 20 ], and efficacy in terms of time-to-target dose. We will also assess the impact of achieving target RAASi dosing on hospital admission rates and duration of stay, with the hope that optimum RAASi treatment will translate into reduced morbidity and improved QoL.…”
Section: Discussionmentioning
confidence: 99%